PENGARUH LOKASI, KUALITAS PRODUK TABUNGAN, KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH DALAM MENABUNG DI BMT ADZKIYAH KHIDMATUL UMMAH DI KOTA METRO - Suwarto, Suwarto; Anggraini, Risa (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2019)
This research is motivated by customer satisfaction which is a customer action to save. The purpose of this study was to determine the ef ect of location, quality of savings products, service quality on customer satisfaction. In this study using primary data collected by explanatory research methods and sample collection techniques in the form of accidental sampling of BMT customers Adzkiyah Khidmatul Ummah using a questionnaire with a likert skla in BMT Adzkiyah Khidmatul Ummah in Metro City. Testing the instrument requirements used include validity, reliability testing. Requirements analysis using normality test, linearity test, homogeneity test. And analysis tools using multiple linear regression with partial test (t test), simultaneous test (f test), coef icient of determination test (R2). As testing requirements analysis and hypothesis testing. Based on the results of research using multiple linear regression analysis obtained location influences customer satisfaction, the quality of savings products does not af ect customer satisfaction, and service quality influences customer satisfaction.